The perfect Nazi : uncovering my grandfather's secret past - Davidson, Martin P. 1960- (G.P. Putnam's Sons, 2011)
What if you found out that your grandfather--the man who had been a demanding, magnetic presence throughout your childhood--was a Nazi SS officer? This is the confession that Martin Davidson, already into middle age, received from his mother upon his grandfather Bruno Langbehn's death, and this is Davidson's exploration, using the skills he honed as a documentary producer for the BBC, of the truth behind this dark family secret. As Martin dove into his research, drawing on a cache of personal documents as well as eyewitness accounts of this historical period, he learned that Bruno's story moved lockstep in time with the rise and fall of the Nazi party, and realized that his grandfather was in many ways the "perfect Nazi," his individual experiences emblematic of the generation of Germans who would plunge the world into such darkness.--From publisher description